EVALUASI STRATEGI KOMUNIKASI KEMENTERIAN DESA-PDTT DALAM MEMBANGUN AWARENESS PROGRAM INOVASI DESA TAHUN 2018-2019 (STUDI KASUS DI KABUPATEN SUKABUMI, JAWA BARAT) - WIBOWO, PRASETYO EDHO (Jurnal Visi Komunikasi, 2022)
Villages are an important part of community development that cannot be separated. The importance of village development has received the attention of various experts in rural planning. The existence of the village is the forerunner to the development of a country that dares to build from the smallest things in the government structure. The village innovation program is designed to encourage and facilitate the strengthening of village capacity that is oriented towards meeting the achievement of the targets of the mediumterm development plan (RPJMN). This research refers to the communication strategy which is the best combination of several communication elements starting from the communicator and message content. The method that the researcher uses in this discussion is a case study in Girimukti Village, Ciemas District, Sukabumi Regency, West Java with a qualitative approach. The results of the study indicate that it can be concluded that the communication strategy carried out by the Ministry of Villages-PDTT towards the Village Innovation Program focuses on two communication strategies. Namely direct and indirect communication. In direct communication, the Ministry of Villages-PDTT chooses mass media, while indirect communication focuses on structural communication strategies.